2022
DOI: 10.1016/j.jhazmat.2021.126768
|View full text |Cite
|
Sign up to set email alerts
|

Plant uptake of perfluoroalkyl substances in freshwater environments (Dongzhulong and Xiaoqing Rivers, China)

Abstract: This study provides new knowledge on the mobility, behavior, and partitioning of 17 perfluoroalkyl substances (PFASs) in the water-sediment-plant system along the Dongzhulong and Xiaoqing Rivers. The fate of PFASs in these rivers is also discussed. The study area is affected by the industrial production of perfluorooctanoic acid (PFOA). The ∑ PFASs in water and sediments close to the industrial discharge were 84,000 ± 2000 ng/L and 2300 ± 200 ng/g dw, respectively, with the concentrations decreasing along the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“… ,,, For example, primidone and phenytointwo relatively stable compoundshave been detected in cabbage and lettuce irrigated with treated wastewater . Likewise, plant uptake and translocation could be an important entry pathway for short-chain per and polyfluoroalkyl substances that are persistent and bioaccumulative in terrestrial systems. Finally, potent systemic insecticides such as fipronil, which can be present in treated wastewater at concentrations as high as 340 ng/L, could undergo plant uptake and translocation because these insecticides are designed to be distributed throughout plants after application to seeds . Attempts to quantify fipronil in the plants from this study were hindered by high background levels of the compound detected in the willow leaves used for matrix matching, low porewater concentrations, and relatively high limits of quantification for the compound.…”
Section: Resultsmentioning
confidence: 99%
“… ,,, For example, primidone and phenytointwo relatively stable compoundshave been detected in cabbage and lettuce irrigated with treated wastewater . Likewise, plant uptake and translocation could be an important entry pathway for short-chain per and polyfluoroalkyl substances that are persistent and bioaccumulative in terrestrial systems. Finally, potent systemic insecticides such as fipronil, which can be present in treated wastewater at concentrations as high as 340 ng/L, could undergo plant uptake and translocation because these insecticides are designed to be distributed throughout plants after application to seeds . Attempts to quantify fipronil in the plants from this study were hindered by high background levels of the compound detected in the willow leaves used for matrix matching, low porewater concentrations, and relatively high limits of quantification for the compound.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have reported that aquatic plants are effective species for PFAS phytoremediation given their high bioaccumulation (RCF > 1) and translocation capacity (transport factor (TF) > 1) [29,30]. Alternanthera sessilis was considered a good phytoremediator of C4-C7 PFCAs in surface water, with mean RCFs and TFs greater than one [31]. To date, research on PFAS uptake and distribution in plants has focused on terrestrial plants and agricultural species.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their unique properties, such as water repellency, chemical durability, and thermal stability, PFAAs have been manufactured for over eight decades and are widely used in various commercial and industrial products . The long-term and widespread usage of PFAAs has resulted in their ubiquitous occurrence in aquatic environments around the world. Sediments, as the essential component of aquatic environments, are expected to be the ultimate sink of PFAAs, particularly possessing high solubility and polar functional groups with concentrations up to the μg/g level. , For instance, the ambient concentration of perfluorooctanoic acid (PFOA) was observed to be 3.64 μg/g dry weight (dw) in sediments collected from the Xiaoqing River Basin, while sediment samples collected from an urban river located in South China exhibited 35 specific PFAAs with a total concentration of 0.85 μg/g dw . Similar significant levels of PFAAs have been found in sediments from other regions, including North America, , the European Union, , and other areas, , and the frequent identification of high levels of PFAAs in sediments around the world is emerging as a prominent trend.…”
Section: Introductionmentioning
confidence: 99%